حماية المال العام واجب شرعي: دراسة تحليلية - Humaid Nasser; Mualimin Mochammad Sahid; Mohd Soberi Awang (Universiti Sains Islam Malaysia, 2024)
Journal of Fatwa Management and Research, Volume 28 Issue 2 Page (175–192)